Impacto de la ley 1314 de 2009 en la actualización de la profesión contable en Colombia. - Benítez Zuluaga, Maira Alejandra; Forero Castañeda, Jessica; Romero Moreno, Lina Johana (Corporación Universitaria Minuto de Dios, 2019)
"Esta investigación busca analizar el impacto que genero la ley 1314 de 2009 en la actualización de la profesión contable en Colombia, y los diferentes mecanismos implementados por el profesional para una adecuada implementación de las normativas internacionales que se requieren en el momento de entrar en vigencia dicha ley. El análisis de la investigación proporciona una reflexión de lo importancia que es para los contadores públicos generen una actualización en las nuevas normas requeridas en el desarrollo de la labor profesional desde la implementación de las NIIF. El proceso de investigación es realizado a través de una metodología mixta con un enfoque de tipo descriptivo, obteniendo así la información de diversas fuentes secundarias, utilizando el método de revisión y análisis documental, sumando al conocimiento adquirido en el proceso académico, algunos antecedentes adquiridos después de aplicar la entrevista a docentes de la universidad UNIMINUTO Virtual a Distancia, siendo la entrevista uno de los instrumentos de recolección de datos."

This research seeks to analyze the impact of gender law 1314 of 2009 on the upgrade of the accounting profession in Colombia, and the different mechanisms implemented by the professional for an adequate implementation of the international norms that are required at the time of entry into force of this law. The analysis of the research provides a reflection of the importance that the public accountants be upgraded to the standards required in the development of the professional work. the research process is conducted through a mixed methodology with an approach of descriptive type, thus obtaining information from various sources, using the method of review and documentary analysis, adding to our knowledge some background acquired by applying the interview to the teachers of the university UNIMINUTO Virtual Distance, as an instrument of data collection. The research is focused on three variables: 1. The need for accounting professionals to generate an update in front of IFRS after the implementation of the law 1314 of 2009. 2. The changes in the professional profile from the implementation of the standard. 3. The mechanisms used by the accounting professionals for the development of the update in the direction of internationalization of the management policy of the accounting profession. This investigative process fosters the proper development of conclusions to our question, providing a vision of how necessary it is to implement an update of the profession after the implementation of IFRS, even when there is no rule that obliges the professional to the update, it is essential not to be left behind compared to the professionals who graduated in the last year mainly.
Analizar el impacto que ha tenido la implementación de la ley 1314 de 2009 en la actualización de la profesión del contador público.
Keywords: Contador; NIIF; Perfil Profesional; Impacto; Ley 1314 del 2009; Accountant; Impact; Law; Professional Profile; Contabilidad; Leyes; Análisis financiero